I2/DMSO-Promoted Synthesis of Chromeno[4,3-b]quinolines through an Imine Formation/Aza-Diels–Alder/Aromatization Tandem Reaction under Metal-Catalyst- and Photosensitizer-Free Conditions - Peñaranda Gómez, Angélica; Puerto Galvis, Carlos E.; Macías, Mario A.; Ochoa-Puentes, Cristian; Kouznetsov, Vladimir V. (Synthesis, 2021)
A tandem approach was developed for the efficient synthesis of substituted chromeno[4,3-b]quinolines from arylamines and O-cinnamyl salicylaldehydes under metal-catalyst- and photosensitizer-free reaction conditions. Our protocol is based on an inexpensive I2/DMSO system in which molecular iodine first acts as a Lewis acid to promote the formation of the corresponding imine bearing the alkene moiety; then, this species fulfills a second role by catalyzing an intramolecular aza-Diels–Alder cycloaddition to generate the respective tetrahydrochromenoquinoline as an intermediate. Finally, the dual behavior of DMSO as an oxidant and as a solvent proved crucial at this stage, allowing the regeneration of I2 and promoting the aromatization of the tetrahydrochromenoquinoline intermediates to yield the desired 7-aryl-6H-chromeno[4,3-b]quinolines. This protocol is mild and easy to perform, features high step-economy (tandem process) and provides a new access to biologically important nitrogen- and oxygen-containing heterocyclic molecules.
Keywords: chromeno[4,3-b]quinolines; imines; iodine; tandem reaction; aza-Diels–Alder reaction; oxidation